Toward Dynamic Corporate Stakeholder Responsibility - Sachs, Sybille (Journal of business ethics, 2009)
Today, sustainable relations with a broad range of key stakeholders are not only important from a normative business ethics perspective, but also from an entrepreneurial viewpoint to allow and support the long-term survival of a firm. We will argue that the traditional conception of a firm’s corporate social responsibility does not reflect this view and that a comprehensive and dynamic conception of a firm’s responsibilities is necessary to map the reality of business practice and to manage the challenges implied by sustainability. We think that distributive justice, that is the way in which firms involve their stakeholders in their wealth creation and dissemination processes, provides a comprehensive understanding of corporate responsibilities. Concerning procedural justice, we will discuss how firms involve stakeholders in their strategic processes according to their contribution to wealth creation. In the course of the article, we will propose a framework along with three design principles that can be used for shaping dynamic and comprehensive corporate responsibilities, and which thereby allow a sustainable procedure for changing business and non-business environments.